Tax Policy and National Savings in the United States : A Survey. (IMF Working Papers; Working Paper ;, 1988)
This paper explores how tax policy affects the level and allocation of national savings in the United States. It argues that the effect of taxes on the overall private saving level is relatively small and uncertain and that raising public saving is the most direct and efficient way to raise national saving. However, the tax system has a powerful impact on the composition of savings and investment. The paper suggests various specific tax measures that would not only raise government revenue but also enhance the efficiency of savings and investment.